Influencia de programación radiofónica con contenido bilingüe como mecanismo de interculturalidad para los radioescuchas - Carriel Chacón, Briggit Rosicela (2020)
The following research work entitled ¬ “Influence of radio programming with bilingual content as a mechanism of interculturality for listeners”, aims to analyze the influence of radio programming with bilingual content as a mechanism of interculturality for listeners, which He focused on investigating people through a survey with clear and concise questions, on radio tuning issues and if they have noticed that in our country there are schedules presenting bilingual content and if they have knowledge on the issue of interculturality. And according to the answers given by the population, it was concluded that there are not many radios that have these bilingual spaces and that many people do not know and have no idea about the issue of interculturality, but mentioned that it would be of great influence for the population due that would open the curiosity of the community to know the diversity that is one of the structural characteristics of our reality as a country. That is why it is recommended to manage dialogue with the radios to instill in the importance that they spend programming with bilingual content, in addition to talk in schools or colleges to make known about the issue of interculturality to both parents and students, and In the same way, orienting the intercultural and bilingual theme to people who do not have knowledge about them in order to reaffirm the multicultural reality of each and every one of the nations, while emphasizing respect and the possibility of coexistence between people and cultures